Diminutive nouns and verbs in Slovene compared to their English equivalents - Sicherl, Eva (Slovenski jezik, 2013)
A contrastive analysis of nominal and verbal diminutives in Slovene and English clearly shows that diminutive formation and use of diminutives in Slovene are tied to the morphological characteristics of nouns and verbs, and,consequently, their morphological-lexemic features, whereas the focus of diminutive formation and use in English remains bound to the syntactic use, orrather, the respective syntactic-semantic use of a given lexeme. In all languages, diminutiveness is a basic element of semantic extension, which can,however, be realized predominantly morphologically, as is the case in Slovene, or predominantly syntactically, as is the case in English. As an element of semantic extension, nominal and, more rarely, verbal diminutivenessin Slovene also plays a crucial role in the development of terminologyŽin this case the diminutive as language metaphor gains semantic independence and becomes a technical term, a phenomenon that is practically unknown in English.
Keywords: angleščina; English; glagol; manjšalnice; samostalnik; Slovene; slovenščina; verb